The Effects of Body-Worn Cameras on Police Efficiency: A Study of Local Police Agencies in the United States - Dammert-Guardia, L (SAGE Publications Inc., 2025)
Research on body-worn cameras (BWCs) has burgeoned in recent years. However, much of this research has not examined the effects of this technology on police performance. In this study, we created a novel dataset on police organizational inputs and outputs and assessed the effects that BWCs have on police efficiency. Using a multiple-stage approach, in the first stage, we estimated the efficiency of local police agencies using a robust order-m efficiency model. In the second stage, we assessed the effects of BWCs using a range of matching estimators and an instrumental variable (IV) model. The first-stage results show that police agencies could improve their efficiency by 2% (from a mean efficiency score of 0.98 to 1). The second-stage matching and IV estimates suggest BWC effects on efficiency range between four and six percentage points in our preferred model. The introduction of this significant technological advance has brought many benefits to police agencies. Our findings show that BWCs can help improve police efficiency, yielding significant cost savings to law enforcement. © 2024 Georgia State University